A world of my own a dream diary - Greene, Graham 1904-1991 (Viking, 1994)
Gathers dream fragments that deal with happiness, other writers, intrigue, politics, war, danger, fear, religion, the writing process, travel, reading, science, love, revenge, crime, talking animals, and death. Graham Greene was always deeply interested in the role played by the subconscious in his writing, and the private world of his dreams was one that he nurtured carefully, recording it almost daily in his dream diaries. Selecting from these dream diaries, he prepared this small treasure for publication just before his death in 1991 - a last gift from a great writer to delight and entertain his readers.